Massive Resistance and Media Suppression : the Segregationist Response to Dissent During the Civil Rights Movement - Wallace, David J., 1981- (Law and society (New York, N.Y.), 2013)
"Wallace explores the role and methods of media suppression in the South during the civil rights movement and the southern 'massive resistance' to integration. Segregationists understood the importance of public opinion to defending their social system, and, as a result, desperately fought to influence how the civil rights movement and segregation were defined for the nation. However, when certain national news coverage and the voices of a minority of southern journalists challenged the growing massive resistance extremism and the arguments used to preserve the 'southern way of life, ' segregationists responded with organized attempts to silence criticism, dissent and public debate within the press"--Provided by publisher.